0524 Polysomnographic Characteristics of Adolescent Patients with Class III Obesity and Severe OSA (AHI ≥30). (25th May 2022) - Strang, Abigail; Crain, Benjamin; Nguyen, Linhda; Chidekel, Aaron
Abstract: Introduction: Adolescents with obesity are at increased risk for obstructive sleep apnea (OSA). Polysomnographic characteristics of pediatric patients with severe OSA (defined as AHI ≥30 events/hour) have not been frequently described. This study aims to describe clinical characteristics and polysomnographic data from a cohort of adolescents with both severe (class III, BMI ≥40 kg/m2) obesity and severe OSA. Methods: This IRB-approved, retrospective review examines clinical and polysomnographic data from pediatric patients (ages 8-18) at Nemours Children's Hospital, Wilmington, Delaware, who had initial baseline diagnostic polysomnogram performed from December 2012-September 2021. Subgroup analysis and descriptive statistics were performed in patients with severe OSA (AHI ≥30 events/hour). Results: 259 (mean age 15.2 years, range 8 – 18 years, 64.4% female, 40.2% white, 46.7% black, mean BMI 50.3 kg/m2) pediatric patients with severe obesity completed initial baseline diagnostic polysomnogram in the study period. Of these patients, 41/259 (15.8%) met criteria for severe OSA (mean age mean age 15.4 years, range 12 – 18 years, 43.9% female, 46.3% white, 43.9% black, mean BMI 53.7 kg/m2). Of these studies, the mean total AHI was 65.2 (range 31.4-159.4) events/hr, obstructive apnea index (OAI) of 11.4 (range 0 – 69.4) events/hr and hypopnea index of 47.8 (range 12.9 – 108.8) events/hour. Mean SpO2 nadir was 78.9 (range 52 – 98)% with peak ETCO2 of 53.2 (range 39 – 69) mmHg. 12/41 (29.2%) of patients met polysomnographic criteria for hypoventilation (EtCO2 >50 mmHg for >25% of TST). Sleep architecture was notable for decreased mean sleep efficiency at 62.8% and elevated arousal index (mean 62.4 arousals/hour). Conclusion: Adolescents with both severe OSA and obesity demonstrated a high frequency of hypopneas compared to apneic events and disrupted sleep architecture with high arousal index and decreased sleep efficiency. Interestingly, even among those with severe OSA, ventilation was acceptable in a majority of the patients. Further analysis will be completed to correlate patient clinical characteristics, including co-morbidities and lung function measurements, to help identify which patients with severe obesity are at risk for the most severe OSA. Support (If Any): None